2018
DOI: 10.1371/journal.pone.0203411
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria richness and antibiotic-resistance in bats from a protected area in the Atlantic Forest of Southeastern Brazil

Abstract: Bats play key ecological roles, also hosting many zoonotic pathogens. Neotropical bat microbiota is still poorly known. We speculate that their dietary habits strongly influence their microbiota richness and antibiotic-resistance patterns, which represent growing and serious public health and environmental issue. Here we describe the aerobic microbiota richness of bats from an Atlantic Forest remnant in Southeastern Brazil, and the antibiotic-resistance patterns of bacteria of clinical importance. Oral and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 60 publications
(70 reference statements)
2
47
2
1
Order By: Relevance
“…This study has shown that urban environments play an important role in the dynamics of wildlife-human interactions and increase the frequency of wildlife-to-human transmission. In contrast, in a recent study, Brazilian fruit bats showed a low occurrence of resistance in their enterobacterial microbiota due to the well-preserved environment where the animal was captured [1]. However, the role of fruit bats in wildlife-human interactions is still poorly documented and needs to be more deeply investigated, particularly in the context of anthropogenic environments.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This study has shown that urban environments play an important role in the dynamics of wildlife-human interactions and increase the frequency of wildlife-to-human transmission. In contrast, in a recent study, Brazilian fruit bats showed a low occurrence of resistance in their enterobacterial microbiota due to the well-preserved environment where the animal was captured [1]. However, the role of fruit bats in wildlife-human interactions is still poorly documented and needs to be more deeply investigated, particularly in the context of anthropogenic environments.…”
Section: Introductionmentioning
confidence: 79%
“…Bats are an important, widespread, and abundant taxon of mammals with over 1300 described species [1]. These species are considered as the reservoir of many viruses that periodically spread in human populations during disease outbreaks and whose dynamics need to be fully understood [2].…”
Section: Introductionmentioning
confidence: 99%
“…It's wing morphology (shorter and broader) and flight (low aspect ratio) are characteristic of the phyllostomids, which have diverse diets and can glean prey from the surface of vegetation (Norberg and Rayner , Stockwell ). Phyllostomids that occur at the Atlantic Forest from São Paulo state (Garbino ) and have already been recorded at PECB (Cláudio et al ) include the nectarivore Glossophaga soricina , the frugivore Carollia perspicillata and the insectivore Glyphonycteris sylvestris . Based on general appearance, the same phyllostomid species, which we refer to hereafter as Phyllostomidae species 1, may have depredated the nests of the Atlantic royal flycatchers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cameras and nests were checked every 1–5 d, and recordings were analyzed in the laboratory. Although bat identification based solely on video records is difficult, we attempted identification by comparing the general characteristics of the observed animals with those species reported to occur in the region (Gardner , Garbino , Cláudio et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Bats are natural reservoirs to numerous viruses, capable of causing zoonotic diseases in other mammals, without showing pathological signs of disease themselves (Letko et al, 2020). In recent years, bats are also increasingly recognized as significant reservoirs for antimicrobial-resistant bacterial organisms of human and animal health significance (Claudio et al, 2018;Garces et al, 2019;McDougall et al, 2019;Nowak et al, 2017;Nowakiewicz et al, 2020). Combined with the bats' ability of powered and sustained flight, their geographical ranges, and interactions with other animals, bats are therefore considered a significant threat for the spread of antimicrobial-resistant bacteria and emergence of zoonotic viruses capable of causing disease in humans and domesticated animals.…”
Section: Discussionmentioning
confidence: 99%